LR White is preferable to Unicryl for immunogold detection of fixation-sensitive nuclear antigens - Philimonenko, V V; Janácek, J; Hozák, P (European journal of histochemistry, 2002)
The purpose of this study was to compare two electron microscopy embedding media - LR White and Unicryl - with regard to cell morphologyical and immunohistochemical preservation properties for the study of fixation-sensitive nuclear antigens. Human cervical carcinoma (HeLa) cells were fixed with 2% paraformaldehyde and 0.1% glutaraldehyde, and embedded in parallel in the two resins: LR White and Unicryl using; two different polymerization protocols were used for each resin. Preservation of fine nuclear structure was good after LR White and poor after Unicryl embedding. Immunogold labeling of Sm antigen was significantly stronger on LR White sections. Polymerization by UV light resulted in stronger and more specific labeling than heat polymerization. These results show that LR White is advantageous over Unicryl for the study of nuclear antigens requiring delicate aldehyde fixation.
Keywords: Microscopy, Immunoelectron; Acrylic Resins; akrylové pryskyřice; indikátory a reagencie; antigeny jaderné; imunohistochemie; HeLa buňky; ultrafialové záření; zalévání tkání; Antigens, Nuclear; lidé; Immunohistochemistry; HeLa Cells; Humans; imunoelektronová mikroskopie; Tissue Embedding; Indicators and Reagents; fixace tkání; Ultraviolet Rays; Tissue Fixation